Psychological insulin resistance among patients with diabetes mellitus in Botswana - Engemadzo Bitsang; Billy M. Tsima; Keneilwe Motlhatlhedi (African Journal of Primary Health Care & Family Medicine)
Background: Timely initiation of insulin therapy is vital in patients with type 2 diabetes mellitus. However, insulin initiation may be delayed because of psychological insulin resistance (PIR).